Bimbingan Dan Konseling Belajar: Managemen Waktu Penghafal Al Qur'an Dalam Meraih Prestasi Akademik - Hafisa Idayu (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
Guidance And Learning Counseling: Management Of Al-Qur'an Memorization Time In Achieving Academic Achievement. This study aims to determine the guidance and learning counseling: management of Al-Qur'an memorization time in achieving academic achievement. The method used in this research is a qualitative method with a descriptive approach and discusses the division and timing of an al-Qur'an memorizer in achieving academic achievements. The results of the study showed that in addition to memorizing the Koran, the subject was also able to achieve academic achievement. In research there are 4 ways or methods used by both subjects in using their time to the maximum, namely: setting goals and priorities, planning and scheduling, ability to control time and evaluation.Keywords: Learning, Time Management, Academic Achievement